2019
DOI: 10.1108/jhti-07-2018-0040
|View full text |Cite
|
Sign up to set email alerts
|

The role of social media as a distribution channel for promoting pricing strategies

Abstract: Purpose The purpose of this paper is to investigate how using social media (SM) as a tool to influence demand motivates the distribution of different price promotion strategies to encourage consumers to utilize direct bookings, along with how this impacts revenue strategies and profitability. Design/methodology/approach This study surveyed hotel executives who hold managerial positions and revenue managers with a direct influence on pricing decisions and developed multiple regression analysis models for vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Price is the common factor while buying any product, but it also depends on when it is an ethical product because in ethical manufacturing products, the prices are quite high because every product that is being created, the elements that are being used in making the product is costly due to which ethical products are high in price. Ampountolas et al (2019) revealed that pricing strategies have effect on buying decision and demand of products. Because of that consumer think before purchasing the product as they can make alternative choices by comparing the ethical product by the normal product in the market which could cause an adverse effect in the market of ethical products.…”
Section: Price Factormentioning
confidence: 99%
“…Price is the common factor while buying any product, but it also depends on when it is an ethical product because in ethical manufacturing products, the prices are quite high because every product that is being created, the elements that are being used in making the product is costly due to which ethical products are high in price. Ampountolas et al (2019) revealed that pricing strategies have effect on buying decision and demand of products. Because of that consumer think before purchasing the product as they can make alternative choices by comparing the ethical product by the normal product in the market which could cause an adverse effect in the market of ethical products.…”
Section: Price Factormentioning
confidence: 99%
“…Social media is defined as “a group of internet-based applications that are built on the ideological and technological foundations of Web 2.0, and that allow the creation and exchange of user-generated content (UGC)” (Kaplan and Haenlein, 2010, p. 61). Consumers can use social media to gain social status, prestige and obtain information (Ampountolas et al , 2019; Kang, 2018; Küçükergin and Dedeoğlu, 2014; Xiang and Gretzel, 2010). The desire for prestige and appreciation can motivate people to share their experiences using social media tools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While consumer channel alternatives continue to rise over a growing variety of Internet systems that continue to advance the extended pricing capabilities, alternate means of pricing optimization techniques have been introduced (Anderson, 2012). Nevertheless, we witnessed that the existing practice of everyday hotel operations has been somewhat different (Ampountolas et al, 2019). Hotels encounter challenges because of the pricing complexity and any viable variable pricing initiatives (Bodea and Ferguson, 2014; Phillips, 2005).…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…If the consumer is price-sensitive, they pay less than other consumers. Consumers are myopic, so they buy goods or services shortly as the price is lower than they are willing to pay (Ampountolas et al, 2019). In early papers, Gallego and van Ryzin (1994, 1997) examine the DP approach and optimal pricing decision situation over a given time so that the company can maximize revenue.…”
Section: Background and Hypothesesmentioning
confidence: 99%